SPOT-VEGETATION GEOV1 biophysical parameters in semi-arid agro-ecosystems - Raymaekers, D. (2014)
The VEGETATION system, which has been delivering global observations of the surface on a daily basis since 1998, provides key information for regional to global climate, environmental and natural resource management applications. Just recently, VEGETATION-derived GEOV1 biophysical products (LAI, FAPAR, and FCOVER) became available for the scientific community and were evaluated in this study for semi-arid forests in the Dry Chaco ecoregion, Argentina. Indirect validation with the MODIS-derived biophysical products (MOD15A2) shows a very good temporal consistency between both products for the period 2000-2011, with a remarkably smooth behaviour of the GEOV1 products. A good relationship between both products was found in the regression analysis with an R2 of 0.826 and 0.724 for LAI and FAPAR, respectively. Using direct validation with digital hemispherical photography (DHP) and ceptometer ground measurements, a relatively small RMSE (RMSELAI ≈ 0.31 and RMSEFAPAR ≈ 0.11) was found. The novel PASTIS-57 technique, which can derive continuous plant area index (PAI) estimates from light transmittance measurements, shows a similar temporal profile to the GEOV1 LAI product with a relatively high but constant offset for the dry forest study sites and a nearly identical profile for the deforested site (R2 = 0.86). Overall, PASTIS-57, in combination with satellite-based observations, shows potentials in LAI/PAI research and ecosystem carbon studies in general, but more ground measurements taken over multiple growing seasons and vegetation types are required to confirm these findings.